Hardening effects in plastically deformed Pd with the addition of H. (15th March 2015) - Chen, Y.Z.; Ma, X.Y.; Shi, X.H.; Suo, T.; Borchers, C.; Zhang, K.H.; Liu, F.; Kirchheim, R.
Abstract : Well-annealed Pd and Pd–H alloys were subjected to tensile tests. It is found that the presence of H does not affect the yield strength but enhances the strain hardening of Pd remarkably. This is explained by a negligible solute drag effect of H on the movement of dislocations, and by H-induced enhanced multiplication of dislocations upon plastic deformation, respectively.